STRATEGI PENGELOLAAN KEUANGAN UMKM DALAM MENGHADAPI ERA TRANSISI PANDEMI COVID 19 - Fitriyana, Mifta; Prasojo, Eko (Program Studi Manajemen, 2022)
Financial planning for business actors is important, how in running a business it is necessary to carry out good corporate functions. In a company, management is an important component that must be owned by the company to realize the vision and mission to be achieved, one of which is financial management within the company. Business actors, in this case the focus is on MSMEs, which currently have new challenges, these new challenges emerge of course after the pandemic. With the pandemic, there are a lot of businesses, even business actors